Dynamical analysis and Big Bang bifurcations of 1D and 2D Gompertz’s growth functions - Rocha, J. Leonel (2017)
In this paper, we study the dynamics and bifurcation properties of a three-parameter family of 1D Gompertz’s growth functions, which are defined by the population size functions of the Gompertz logistic growth equation. The dynamical behavior is complex leading to a diversified bifurcation structure, leading to the big bang bifurcations of the so-called “box-within-a-box” fractal type. We provide and discuss sufficient conditions for the existence of these bifurcation cascades for 1D Gompertz’s growth functions. Moreover, this work concerns the description of some bifurcation properties of a Hénon’s map type embedding: a “continuous” embedding of 1D Gompertz’s growth functions into a 2D diffeomorphism. More particularly, properties that characterize the big bang bifurcations are considered in relation with this coupling of two population size functions, varying the embedding parameter. The existence of communication areas of crossroad area type or swallowtails are identified for this 2D diffeomorphism.